{The Sexuality of Adolescents and Young Women With MRKH Syndrome: A Qualitative Study.} - Tsitoura, Anastasia; Michala, Lina (The journal of sexual medicine, 2021)
BACKGROUND: Vaginal agenesis, most commonly referred as Mayer-Rokitansky-Küster-Hauser (MRKH) Syndrome, is mostly diagnosed as primary amenorrhea in teenage girls; although there is plenty of literature concerning the formation of a neovagina, limited research has focused on the psychological burden of this diagnosis to the girls. AIM: To enlighten health providers into the finer aspects of sexuality through the own words and experiences of girls with MRKH under our care. METHODS: Women currently undergoing vaginal dilation or who had completed vaginal dilation within the past year were recruited from February 2019 to January 2020. A gynecologist with training in Sexual Medicine conducted a semistructured interview, which was recorded and then transcribed to identify common themes among interviewees. OUTCOMES: The main outcome explored was the narrative experiences of women with MRKH. RESULTS: 7 women participated, with a mean age of 19.7 (range 17-22 years). None of the girls felt stigmatized, however one reported significant distress at diagnosis, stemming from the attitude of health care professionals and exacerbated by an earlier age at disclosure. All girls accepted that VDT was successful, when it was initiated after they had felt sexual interest and arousal. Exact quantification of the vaginal length at onset, worried 4 as they felt pressurized to achieve a specific length. A few girls reported anxiety over sharing the diagnosis with an intimate partner. All of them pretended at some point to have menses. Childbearing was an important issue for most of the interviewees, but it did not concern them for the time being. All girls had supporting families. However, 5 did not want to share information about VDT with them. One girl reported that openness in discussing genital anatomy, VDT and sexuality, helped her both in completing treatment and adapting in a sexual relationship. CLINICAL IMPLICATIONS: A multidisciplinary team should aim for age-appropriate disclosure and consultation and guide women through VDT and their sexual relations. STRENGTHS AND LIMITATIONS: This is a thorough account of women's perceptions regarding VDT and sexuality in MRKH. However, our conclusions may be limited by the small number of participants. CONCLUSION: Gradual provision of information at disclosure and adjusted timing at VDT may reduce stress in girls with MRKH. Tsitoura A, Michala L. The Sexuality of Adolescents and Young Women With MRKH Syndrome: A Qualitative Study. J Sex Med 2021;18:2012-2019.
Keywords: 46; Abnormalities; Adolescent; Adult; Congenital Abnormalities; Female; Humans; Mullerian Ducts; psychology; Sexual Behavior; Sexuality; therapy; Vagina; XX Disorders of Sex Development; Young Adult